Metatarsal Shaft Fracture with Associated Metatarsophalangeal Joint Dislocation - Taranjit Singh Tung (Case Reports in Orthopedics)
Metatarsophalangeal joint dislocations of lesser toes are often seen in the setting of severe claw toes. Traumatic irreducible dislocations have been reported in rare cases following both low-energy and high-energy injuries to the forefoot. In this case report, I present a previously unreported association of a metatarsal shaft fracture with metatarsophalangeal joint dislocation of a lesser toe.